Epigenetics and precision medicine in cardiovascular patients: from basic concepts to the clinical arena. (23rd October 2017) - Costantino, Sarah; Libby, Peter; Kishore, Raj; Tardif, Jean-Claude; El-Osta, Assam; Paneni, Francesco
Abstract: Cardiovascular diseases (CVDs) remain the leading cause of mortality worldwide and also inflict major burdens on morbidity, quality of life, and societal costs. Considering that CVD preventive medications improve vascular outcomes in less than half of patients (often relative risk reductions range from 12% to 20% compared with placebo), precision medicine offers an attractive approach to refine the targeting of CVD medications to responsive individuals in a population and thus allocate resources more wisely and effectively. New tools furnished by advances in basic science and translational medicine could help achieve this goal. This approach could reach beyond the practitioners 'eyeball' assessment or venerable markers derived from the physical examination and standard laboratory evaluation. Advances in genetics have identified novel pathways and targets that operate in numerous diseases, paving the way for 'precision medicine'. Yet the inherited genome determines only part of an individual's risk profile. Indeed, standard genomic approaches do not take into account the world of regulation of gene expression by modifications of the 'epi'genome. Epigenetic modifications defined as 'heritable changes to the genome that do not involve changes in DNA sequence' have emerged as a new layer of biological regulation in CVD and could advance individualized risk assessment as well as devising and deploying tailored therapies. This review, therefore, aims to acquaint the cardiovascular community with the rapidly advancing and evolving field of epigenetics and its implications in cardiovascular precision medicine.